Нейромережеве моделювання процесів розпізнавання графічних схем - Чічірін, Є.М.; Сосненко, К.П. (Комп’ютерні засоби, мережі та системи, 2019)
Розроблена нейромережева модель розпізнавання графічних примітивів – вузлів у складі засобів синтаксичного аналізу зображень блок-схем. Сформована базова множина навчальних зображень вузлів БС. Розглянуто етапи програмного синтезу навчальних даних, а також аугментації синтетичних навчальних даних. Запропоновано нейромережеві моделі для підвищення точності детектування вузлів БС на основі повнозв'язаних мереж та загорткових нейронних мереж без шарів субдескретизації. Разработана нейросетевая модель распозна-вания графических примитивов – узлов в составе средств синтаксического анализа изображений блок-схем. Сфор-мировано базовое множество обучающих изображений узлов БС. Рассмотрены этапы программного синтеза обучающих данных, а также аугментации синтетических учебных данных. Предложены нейросетевые модели для повышения точности детектирования узлов БС на основе полносвязных сетей и сверточных нейронных сетей без слоев субдискретизаци A neural network model has been developed for recognizing the graphic listed primitives - nodes as part of the tools for parsing graphic images of flowcharts. A basic set of training and test images of BS nodes has been formed. The stages of the software synthesis of training data, as well as the augmentation of synthetic training data for their reproduction, are considered. It is noted that it is necessary not only to classify the node, but also to localize its position, since the reliability of the successful detection of each next node is determined by the accuracy of the combination of the center of the scan window and the center of the real node. Neural network models are proposed to increase the accuracy of detection of flowchart nodes based on fully accessible and convolutional neural networks without layers of subsampling. The expediency of combining syntactic and neural network recognition methods for a wide class of graphic images is substantiated.